Delayed and incomplete treatment may result in dural fistula development in children with Vein of Galen malformation - Meila, Dan (Interv Neuroradiol, 2017)
The association of dural arteriovenous fistulas (DAVF) in children with Vein of Galen malformation (VGM) has recently been reported for the first time. In a larger series of cases treated with transarterial NBCA embolization, 30% had DAVF. We wanted to analyze the development of DAVF in our cohort of children with VGM and to evaluate whether their occurrence depends on different treatment timing and embolic materials. We analyzed 43 VGM cases treated with a combined transarterial and transvenous approach between 2003 and 2016. In our early series until 2011, we used coils solely in 21 children. Since 2012, 22 children were treated with the combination of coils and Onyx. In the early series treated with coils solely, no case presented initially with or developed DAVF over time on follow-up angiograms. In our recent series we found four cases (9%) with DAVF. In two patients (5%), DAVF were found on the initial angiogram. Both patients presented at our department at age >2 years and were not treated elsewhere before. One patient (2%) presented at our department with too proximal occlusion of arterial feeders performed at another institution before. Only one patient (2%) developed DAVF in our department after the transarterial use of Onyx. Interestingly, this child did not develop DAVF as long as we used coils solely and his DAVF was localized exactly where an Onyx cast was identified. In conclusion, delayed and incomplete treatment may have a considerable impact on the occurrence of DAVF in VGM.